(3GdJLGQI GdNGQLjI (B:s (3HefXhQ Ydej eJbOe (B/s - (3GdeTgOGfj, NGdO GMeO aQMGfs ((3YeGf(B: s (3OGQ GdGjGe ddfTQ hGdJhRjY(B, s, 2017)
-(3eaghe hJYQja hGgejI GdJLGQI GdNGQLjI (B-(3CSGdjH Jehjd GdJLGQI GdNGQLjI (B-(3CSS ddYdGbGJ GdGbJUGOjI GdOhdjI (B-(3GdJLGQI GdOhdjI (B-(3CKQ GdJLGQI GdOhdjI Ydi GdHjFI (B-(3OhQ GdJLGQI GdOhdjI aj NWI GdJfejI deG HYO YGe (B2015 -(3JcdaI GdEfJGL GdfSHjI (B-(3GdYdGbI Hjf GdJLGQI GdNdGQLs
(3HHdjhZQGajG(B:(3U(B.557s
Keywords: (3GdJLGQI GdNGQLjIs; (3GdJLGQI GdOhdjIs